2013
DOI: 10.1111/1574-6941.12148
|View full text |Cite
|
Sign up to set email alerts
|

454 pyrosequencing analyses of bacterial and archaeal richness in 21 full-scale biogas digesters

Abstract: The microbial community of 21 full-scale biogas reactors was examined using 454 pyrosequencing of 16S rRNA gene sequences. These reactors included seven (six mesophilic and one thermophilic) digesting sewage sludge (SS) and 14 (ten mesophilic and four thermophilic) codigesting (CD) various combinations of wastes from slaughterhouses, restaurants, households, etc. The pyrosequencing generated more than 160,000 sequences representing 11 phyla, 23 classes, and 95 genera of Bacteria and Archaea. The bacterial comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

65
387
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 652 publications
(459 citation statements)
references
References 58 publications
65
387
4
3
Order By: Relevance
“…This result was consistent with the previous studies [45][46][47]. This high diversity might suggest that a variety of bacterial communities participated in multiple metabolic pathways of organic matter degradation under seasonal temperature variation.…”
Section: Shifts In Microbial Community Structures With Seasonal Tempesupporting
confidence: 93%
See 3 more Smart Citations
“…This result was consistent with the previous studies [45][46][47]. This high diversity might suggest that a variety of bacterial communities participated in multiple metabolic pathways of organic matter degradation under seasonal temperature variation.…”
Section: Shifts In Microbial Community Structures With Seasonal Tempesupporting
confidence: 93%
“…The predominant bacteria in the AWFR system during the whole operation period were grouped into four phyla affiliated with Firmicutes, Proteobacteria, Bacteroidetes, and Chloroflexi, which occupied 89.3 ± 4.08% of the total phyla ( Figure 9). These dominant phyla were also detected in the full-scale biogas digesters [47,48]. During the start-up period, the predominant microorganisms in the AWFR system belonged to the phylum Proteobacteria, Firmicutes, Bacteroidetes and Chloroflexi, with a relative abundance of 33.01%, 22.19%, 19.94% and 11.29%, respectively.…”
Section: Shifts In Microbial Community Structures With Seasonal Tempementioning
confidence: 83%
See 2 more Smart Citations
“…Previous studies showed that archaea accounted for up to 20 % in anaerobic digesters Sundberg et al 2013). In this study, though the primer set should cover most methanogens, the highest relative abundance of Euryarchaeota only accounted for 4.85 % of total reads.…”
Section: Discussionmentioning
confidence: 75%